Microleakage of Teeth Restored with Different Adhesive Dowel Systems: An In Vitro Study - Sari, Tugrul; Ozyesil, Atilla G. (My University, 2014)
PurposeCommercial fiber-reinforced dowel systems are marketed as having better adhesion and sealing ability than conventional metallic dowel systems. The aim of this in vitro study was to evaluate the microleakage of teeth restored with nine dowel systems.